Protein-Protein Interactions in Alpha-Synuclein Biogenesis: New Potential Targets in Parkinson’s Disease - Hernandez, Sarah M.; Tikhonova, Elena B.; Karamyshev, Andrey L. (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease is a debilitating neurodegenerative disorder defined by a loss of dopamine-producing neurons in the substantia nigra in the brain. It is associated with cytosolic inclusions known as Lewy bodies. The major component of Lewy bodies is aggregated alpha-synuclein. The molecular mechanism of alpha-synuclein aggregation is not known. Our conceptual model is that alpha-synuclein aggregates due to a dysregulation of its interactions with other protein partners that are required for its biogenesis. In this review, we identified alpha-synuclein interactions using both current literature and predictive pathway analysis. Alterations of these interactions may be crucial elements for molecular mechanism of the protein aggregation and related pathology in the disease. Identification of alpha-synuclein interactions provides valuable tools to understand Parkinson’s disease pathology and find new pharmacological targets for the disease treatment.